Introduction: Islamic Law in South-East Asia - Hooker, MB. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2003)
In this paper the author confines herself to a specific set of material so as to narrow the issue. All too often this is not done and, as a consequence, argument very quickly degenerates into generalities, mostly driven by personal and/or political bias. Such is illustrated in Ahmad's discussion of Western feminist comment on Islam, Muslim women and human rights where, in quite influential books, we find a combination of inappropriate theory with no understanding of fiqh. The theory looks convincing to a Western reader because it is Western. The insidious nature of the assumptions involved is demonstrated in Ahmad's discussion of Iranian and Malaysian Muslim feminist writings in which we can find an